ANALYSIS OF A SMALL SAMPLE OF EXPERIMENTAL DATA IN THE MANAGEMENT OF GAS CONSUMPTION IN THE REGION - A. M. Kumaritov; A. E. Dzgoev; R. B. Sharibov (Известия высших учебных заведений: Проблемы энергетики)
Analysis of a small sample of experimental data on gas consumption population, allowing to make the right decisions for forecasting of gas consumption in the management of gas supply to the region. Developed new helpful adequate regression models, which are used for forecasting gas consumption.